Safety of immune checkpoint inhibitor rechallenge after severe immune-related adverse events: a retrospective analysis - Eldani, Céline; Kostine, Marie; Faure, Maxime; Lazaro, Estibaliz; Rigothier, Claire; Hiriart, Jean Baptiste; Teulières, Bérénice; Poullenot, Florian; Haissaguerre, Magalie; Zysman, Maeva; Veillon, Rémi; Vergnenegre, Charlotte; et al. (Frontiers in Oncology, 2024)
Immune checkpoint inhibitors (ICIs) present clinicians with the challenge of managing immune-related adverse events (irAEs), which can range from mild to severe due to immune system activation 1. While guidelines recommend discontinuing ICIs for grade 3 partial and all grade 4 irAEs, there is growing interest in rechallenging patients based on oncological outcomes, particularly for cardiovascular and neurological irAEs where data remains scarce 1,2. We retrospectively evaluated the safety of ICI rechallenge following grade 3-4 irAEs, specifically focusing on cardiovascular and neurological events, in patients discussed at our multidisciplinary immunotoxicity assessment board between 2019 and 2021. Fifteen patients were included, with a median time to severe irAE onset of 49 days. Among them, five patients experienced neurological adverse events (NAEs): aseptic meningitis (3), inflammatory polyradiculoneuropathy (1), and ophthalmoplegia (1), while one patient presented with myocarditis. Of the 15 patients retreated with ICIs after initial severe irAEs, 11 (73%) remained free of subsequent irAEs, two (13%) experienced recurrence of the initial irAE, and two (13%) developed new irAEs distinct from the initial event. The median time to event recurrence was 69 days, occurring no earlier than the initial severe irAE. In the subset analysis focusing on severe cardiovascular and neurological irAEs, rechallenge with ICIs was generally well tolerated. However, one patient treated with anti-PD1 experienced a relapse of grade 2 aseptic meningitis. Overall, our findings suggest that rechallenging with ICIs after severe irAEs, including those affecting the cardiovascular and neurological systems, may be safe, particularly after irAE regression and corticosteroid withdrawal.